2021
DOI: 10.1080/10872981.2021.2010291
|View full text |Cite
|
Sign up to set email alerts
|

First-generation and continuing-generation college graduates’ application, acceptance, and matriculation to U.S. medical schools: a national cohort study

Abstract: Many U.S. medical schools conduct holistic review of applicants to enhance the socioeconomic and experiential diversity of the physician workforce. The authors examined the role of first-generation college-graduate status on U.S. medical school application, acceptance, and matriculation, hypothesizing that first-generation (vs. continuing-generation) college graduates would be less likely to apply and gain acceptance to medical school.Secondary analysis of de-identified data from a retrospective national-cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Applicants were categorized as first-generation university applicants when none of their parents had attended higher education, i.e., university or higher vocational education. First-generation university applicants were a subgroup of interest, because previous research has demonstrated that their odds of being selected into medical school are lower (Mason et al, 2021 ; Stegers-Jager et al, 2015 ). Additionally, they face numerous obstacles when applying to medical school, including a lack of knowledge about the admission process and financial barriers (Romero et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Applicants were categorized as first-generation university applicants when none of their parents had attended higher education, i.e., university or higher vocational education. First-generation university applicants were a subgroup of interest, because previous research has demonstrated that their odds of being selected into medical school are lower (Mason et al, 2021 ; Stegers-Jager et al, 2015 ). Additionally, they face numerous obstacles when applying to medical school, including a lack of knowledge about the admission process and financial barriers (Romero et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…10 To diversify the physician workforce, admissions committees should consider making the MCAT optional or pass-fail, and placing greater emphasis on other criteria. 11 Schools using holistic review are more likely to examine other non-academic criteria such as socioeconomic status, 12 experience working with disadvantaged populations, and mission alignment (eg, focus on underserved rural or urban communities). 13,14 Some physician assistant programs examine measures of humanistic and collaborative skills including applicants' experience as patient educators, community organizers, or working at community-based organizations.…”
Section: Alternative Metricsmentioning
confidence: 99%
“…5 To date, most research has centered on FGLI undergraduates, with little data pertaining to graduate students. 6 Medical schools have outlines for the competencies and knowledge they expect students to garner. However, there are other skills that must be cultivated to utilize the full resources of medical school and position oneself for residency.…”
Section: Introductionmentioning
confidence: 99%